2016
DOI: 10.1111/resp.12768
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with radiologic progression of non‐cystic fibrosis bronchiectasis during long‐term follow‐up

Abstract: Background and objective: Non-cystic fibrosis (CF) bronchiectasis is a chronic airway inflammatory disease, exhibiting a diverse array of clinical courses. The purpose of this study was to determine the factors that predict radiologic progression of non-CF bronchiectasis during a long-term follow-up. Methods: We reviewed the electronic medical records that included pulmonary function test data from non-CF bronchiectasis patients, who were older than 18 years of age with a follow-up of computerized tomography f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…P. aeruginosa and H. influenza were the major pathogens in the postinfection and COPD groups, whereas NTM was the most common pathogen in post-tuberculosis group. Several groups have reported variable prevalence of NTM infection in Asia (2-4% in southern China and 44.5% in South Korea) [4,43]. The specific microbiology spectrum of different etiologies has been reported in an Indian population cohort, in which post-infection, post-tuberculosis and idiopathic groups grew more species of cultured bacteria and P. aeruginosa, Enterobacteriaceae species and S. aureus were the most common pathogens, while NTM was uncommon in the cohort [14].…”
Section: Discussionmentioning
confidence: 94%
“…P. aeruginosa and H. influenza were the major pathogens in the postinfection and COPD groups, whereas NTM was the most common pathogen in post-tuberculosis group. Several groups have reported variable prevalence of NTM infection in Asia (2-4% in southern China and 44.5% in South Korea) [4,43]. The specific microbiology spectrum of different etiologies has been reported in an Indian population cohort, in which post-infection, post-tuberculosis and idiopathic groups grew more species of cultured bacteria and P. aeruginosa, Enterobacteriaceae species and S. aureus were the most common pathogens, while NTM was uncommon in the cohort [14].…”
Section: Discussionmentioning
confidence: 94%
“…South Korea has a different distribution with high NTM (44.5%), similar to that of the US and lower rates of P. aeruginosa (18.1%). Like the Thai patients, South Koreans also had a significant prevalence of K. pneumoniae [97]. While geographically close; work from Japan however reports P. aeruginosa as the predominant airway bacteria (24%) closely followed by only moderate levels of NTM (19%) [37].…”
Section: The Bronchiectasis Bacteriome In the Asia-pacific Regionmentioning
confidence: 90%
“…We agree that further studies are needed to validate the Bhalla score in non‐cystic fibrosis (CF) patients. In our study, about one‐third of the study population showed radiological deterioration of bronchiectasis with the Bhalla score system . Although an overall change of the Bhalla score from 9.5 to 10.1 points might not be considered significant by some, the increase in the score in the radiological deterioration group might have radiological importance.…”
mentioning
confidence: 52%